Pendampingan Perancangan Sajian Khas pada Kawasan Wisata di Kecamatan Jangkar Kabupaten Situbondo - Amilia, Winda; Rokhani, Rokhani; Suryaningrat, Ida Bagus; Suryadharma, Bertung (Universitas Nusantara PGRI Kediri, 2023)
Gadingan is a village in Jangkar – Situbondo. It has the potential natural resources known as Gadingan Mas which will be developed as a traditional culinary center, although the type of dishes that has the potential as special culinary delights is not yet known. The purpose of this community empowerment is to assistance Pokdarwis to identify and promoting the special traditional culinary. Participatory rural appraisal (PRA) is applied to encourage village communities to share with each other about the actual situation of the village and to determine development plans and actions. The identification results show that the dishes commonly served in local households are grilled fish, smoked fish, “nasi sodu”, and lamtoro coffee. Using the focus group discussion method, it was decided that Nasi Sodu and Lamtoro Coffee were presented as special culinary delights. A special culinary modification dish is in the form of serving “nasi sodu” with a touch of red and green. This color comes from the use of “sambal cengi” as an additional dish. The addition of this “sambal cengi”, in addition to providing a delicious taste to the “nasi sodu”, also provides a better perception for consumers.